Using a Wearable Brain Activity Sensing Device in the Treatment of Long COVID Symptoms in an Open-Label Clinical Trial - Ryan T. Hurt; Ravindra Ganesh; Darrell R. Schroeder; Jennifer L. Hanson; Shawn C. Fokken; Joshua D. Overgaard; Brent A. Bauer; Bright P. Thilagar; Christopher A. Aakre; Sandhya Pruthi; Ivana T. Croghan (Journal of Primary Care & Community Health)
Objective: This study evaluated the feasibility and satisfaction of using a wearable brain activity sensing device for stress reduction among patients experiencing Long COVID (LC). Patients and Methods: Patients with LC (N = 45) were invited to participate in an open-label pilot study. Participants were asked to use a brain-sensing electroencephalogram (S-EEG) wearable device (Muse-S™) daily for 90 days and followed for an additional 90 days (180 days total participation). Study enrollment began June 28, 2022, and ended July 28, 2023. Results: Patients were predominantly female (82%), white (96%), and with an average age of 47.6 (±12.5) years. At the end of treatment (90 days), cognition, sleep, self-efficacy, and quality-of-life quality of life improved ( P  < .001 to P  = .04). In addition, stress and anxiety were significantly reduced ( P  < .001). These significant changes persisted by end-of-study (180 days). For stress ( P  = .023) and anxiety ( P  = .033), a change from the baseline during follow-up was significantly associated with the amount of S-EEG usage. The end-of-study satisfaction survey indicated that patients were very satisfied with the S-EEG device, and 97% planned to continue using it. Conclusion: Results suggest that the S-EEG device improved cognition in LC, which is one of the main severe symptoms we see in our LC clinic. In addition, it helped reduce stress and anxiety. These findings have important clinical implications for LC patients using S-EEG as an adjunct to concurrent LC clinical care which includes pharmacotherapies.